2019
DOI: 10.1177/2050640619845986
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplant for Crohn disease: A study evaluating safety, efficacy, and microbiome profile

Abstract: Background Emerging trials suggest fecal microbiota transplantation (FMT) is a promising treatment for ulcerative colitis; however, there is a paucity of data in Crohn disease (CD). Objective The objectives of this article are to determine whether single-dose FMT improves clinical and endoscopic outcomes in CD patients and to identify meaningful changes in the microbiome in response to FMT. Methods We performed a prospective, open-label, single-center study. Ten CD patients underwent FMT and were evaluated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 18 publications
0
47
0
2
Order By: Relevance
“…Crohn’s disease (CD) is a chronic inflammatory disease that is considered to result from a complex interplay between genetic susceptibility, environmental factors and altered gut microbiota. The therapeutic potential of faecal microbiota transplantation (FMT) in CD has recently been demonstrated (Gordon and Harbord, ; Kao et al , ; Suskind et al , ; Cui et al ., ; Vaughn et al , ; Gutin et al , ). In our pilot study between 2012 and 2014, 86.7% and 76.7% of patients with refractory CD achieved clinical improvement and remission at 1 month after a single FMT through mid‐gut respectively (Cui et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…Crohn’s disease (CD) is a chronic inflammatory disease that is considered to result from a complex interplay between genetic susceptibility, environmental factors and altered gut microbiota. The therapeutic potential of faecal microbiota transplantation (FMT) in CD has recently been demonstrated (Gordon and Harbord, ; Kao et al , ; Suskind et al , ; Cui et al ., ; Vaughn et al , ; Gutin et al , ). In our pilot study between 2012 and 2014, 86.7% and 76.7% of patients with refractory CD achieved clinical improvement and remission at 1 month after a single FMT through mid‐gut respectively (Cui et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…The evidence on the effect of FMT in CD has recently been presented. There are currently several active trials studying the effectiveness of FMT for CD, and the results are diverse ( Table 2) (Cui et al, 2015;Suskind et al, 2015;Wei et al, 2015;Vaughn et al, 2016;Vermeire et al, 2016;Goyal et al, 2018;Gutin et al, 2019;Sokol et al, 2020;Xiang et al, 2020). Xiang et al (2020) studied 174 CD patients treated with FMT via Mid-gut including nasojejunal tube, endoscopy and mid-gut TET (except one through colonic TET).…”
Section: Crohn's Diseasementioning
confidence: 99%
“…First study showed that FMT was safe and no serious adverse events were observed. However, in the second study 2 out of 10 patients they occured in significant level [31,32] Sixty-nine patients with CD who underwent and responded to FMT in the past were enrolled in Pan Li et al study. This study aimed to evaluate the optimal timing for performing FMT second time to maintain the long-term clinical effects in patients with CD.…”
Section: The Use Of Fmt In Crohn's Diseasementioning
confidence: 99%